Retracted article: Kiseleva I.A., Gryzunova N.V., Anh B.N. Tourism market: pricing issues. Statistics and Economics. 2016;(3):64-69. (In Russ.) DOI:10.21686/2500-3925-2016-3-64-69 - article Editorial (Статистика и экономика)
This article by Irina A. Kiseleva, Natalya V. Gryzunova, Bui Ngoc Anh has been retracted (i.e. withdrawn from the press) by the editor with permission of the publisher.Retracted article due to duplicate publication.